Types of colorectal cancer and dysplasia associated with inflammatory bowel disease - Almottowa, Hisham Abdullah; Alkhars, Abdulmohsen Yaseer; Hassan, Maram Hussam; Alhamad, Hamad Adel; Alshammari, Saad Munawwikh; Bahamdeen, Anas Adel; Ladnah, Tariq Mohammed; Alalyani, Yousef Thalib; Al binmaan, Ahmed Taher; Alajam, Sultan Ali; Alzooabi, Ahmed Abdullah (International Journal Of Community Medicine And Public Health, 2022)
Ulcerative colitis (UC) and Crohn’s disease (CD) are two major inflammatory disorders of the intestinal wall collectively known as inflammatory bowel disease (IBD). Colorectal carcinoma (CRC) is the most significant and grave consequence of IBD and is preceded by dysplasia in majority of the cases. In this review we aim to discuss the various types of dysplasia found in patients with CRC due to IBD. A thorough literature search was conducted in online databases such as PubMed, Google Scholar, from which all studies published in the last ten years were included in this review. The major development in diagnostic procedures and visualization modalities have aided our understanding of dysplasia, which is now known to be the strongest predictor and marker for CRC development. However, the unpredictable behavior and progression of dysplasia still warrants vigilant surveillance. Dysplasia has been classified on histological characteristics using grades of dysplasia from ‘negative for dysplasia’ to ‘high grade dysplasia’. On visibility via an endoscope from ‘visible dysplasia’ to ‘invisible dysplasia’ and macroscopic features of ‘conventional dysplasia’ and ‘non-conventional dysplasia’. No single classification can be utilized to define the stage of dysplasia and more importantly predict its progression and outcome of CRC. Using evidence-based medicine an integrated classification expanding on a management algorithm must be formulated by a panel of experts to steer management of the disease. A multidisciplinary, tailored approach with a strong emphasis on regular and timely surveillance to ensure early detection of CRC can enhance quality of life and patient outcomes.